2022
DOI: 10.1111/jcmm.17239
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of potential biomarkers and therapeutic targets in ferroptosis from coronary artery disease

Abstract: Coronary artery disease (CAD) is a type of disease in which the lumen is narrowed or blocked due to atherosclerotic lesions in the coronary artery, resulting in myocardial ischaemia, oxygen deprivation and necrosis. CAD is one of the highest mortality diseases in the world, with an estimated 12 million deaths due to coronary atherosclerosis by the end of 2030, including non-ST-segment elevation myocardial infarction and ST segment elevation myocardial infarction. 1 The pathogenesis of CAD is complex, and there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 57 publications
0
25
1
Order By: Relevance
“…Nuclear receptor coactivator 4 (NCOA4) recognizes intracellular after ferritin recognition, and ferritin transfers stored ferric ions to the autophagosome for degradation, which, in turn, releases ferric ions into the cytoplasm to become free iron, a process also known as iron autophagy ( 59 , 60 ). In addition, genes such as nuclear receptor coactivator (NRF2) and heat shock protein B1 have been found to affect the sensitivity of cells to ferroptosis inducers by regulating intracellular iron ion metabolism ( 61 , 62 ). This shows that iron ion metabolism is a potential regulatory point for the induction of cellular ferroptosis.…”
Section: Ferroptosismentioning
confidence: 99%
“…Nuclear receptor coactivator 4 (NCOA4) recognizes intracellular after ferritin recognition, and ferritin transfers stored ferric ions to the autophagosome for degradation, which, in turn, releases ferric ions into the cytoplasm to become free iron, a process also known as iron autophagy ( 59 , 60 ). In addition, genes such as nuclear receptor coactivator (NRF2) and heat shock protein B1 have been found to affect the sensitivity of cells to ferroptosis inducers by regulating intracellular iron ion metabolism ( 61 , 62 ). This shows that iron ion metabolism is a potential regulatory point for the induction of cellular ferroptosis.…”
Section: Ferroptosismentioning
confidence: 99%
“…The highlights of our study are the innovative combination of Lasso and RF methods and the excellent results produced in terms of predictive power. The feature selection method of Lasso (38)(39)(40)(41) and RF (42-45) has been widely used in biology as a way to better identify key biomarkers. Before that, there is still no study to construct a prediction model for SLE based on gene sequencing, especially since our study is based on whole blood samples from SLE patients, which are easy to obtain and manipulate.…”
Section: A B Cmentioning
confidence: 99%
“…As for axonal Charcot-Marie-Tooth disease, a cohort study from Italy showed that HSPB1 mutation account for about 4% clinical identified CMT2 patients [ 13 ]. HSPB1, as an important chaperone protein, is also closely related to a variety of other diseases, including lung cancer, colorectal cancer, diabetes, ocular diseases, coronary heart disease and atrial fibrillation [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%